2001
DOI: 10.1359/jbmr.2001.16.5.814
|View full text |Cite
|
Sign up to set email alerts
|

ADAM8: A Novel Osteoclast Stimulating Factor

Abstract: We used polymerase chain reaction (PCR)-selective complementary DNA (cDNA) subtraction hybridization with an immortalized murine osteoclast (OCL) precursor cell line to identify genes that are highly expressed in OCLs compared with OCL precursors and which may be involved in the OCL differentiation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 23 publications
6
100
1
Order By: Relevance
“…In agreement with these earlier studies, the novel D14 0 isoform identified in this report showed a marked increase in the induction of TRAP þ cells. Previous studies have described a 65 kDa human soluble isoform and a 70 kDa truncated murine isoform of ADAM8, structurally similar to the D14 0 isoform (Choi et al, 2001, Mandelin et al, 2003. This soluble murine ADAM8 isoform induced the formation of boneresorbing osteoclasts and acted at later stages of osteoclast differentiation and precursor fusion (Choi et al, 2001).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In agreement with these earlier studies, the novel D14 0 isoform identified in this report showed a marked increase in the induction of TRAP þ cells. Previous studies have described a 65 kDa human soluble isoform and a 70 kDa truncated murine isoform of ADAM8, structurally similar to the D14 0 isoform (Choi et al, 2001, Mandelin et al, 2003. This soluble murine ADAM8 isoform induced the formation of boneresorbing osteoclasts and acted at later stages of osteoclast differentiation and precursor fusion (Choi et al, 2001).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have described a 65 kDa human soluble isoform and a 70 kDa truncated murine isoform of ADAM8, structurally similar to the D14 0 isoform (Choi et al, 2001, Mandelin et al, 2003. This soluble murine ADAM8 isoform induced the formation of boneresorbing osteoclasts and acted at later stages of osteoclast differentiation and precursor fusion (Choi et al, 2001). The fact that this murine form was structurally and functionally related to the D14 0 isoform, which also exhibited a similar pro-osteoclastogenic effect, emphasizes the relevance of ADAM8 in osteoclastogenesis (Choi et al, 2001, Mandelin et al, 2003, Rao et al, 2006, Verrier et al, 2004.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations